High solid and wet anaerobic digestion technologies for the treatment of the organic fraction of municipal solid wastes and food wastes: A comparative case study in Brazil - Silva-Martinez, Rodolfo D; Sanches Pereira, Alessandro; Ornellas-Ferreira, Bernardo; Breno, Carneiro-Pinheiro; Suani, Teixeira Coelho (Elsevier, 2023)
This study evaluates and compares the resource, energy, and GHG emission performance of two biodigestion plants in Brazil, that treat the organic fraction of municipal solid waste (OFMSW); one operating under high solid anaerobic digestion (HSAD) and the other as a wet anaerobic digestion (WAD) system. The results indicate that the HSAD system: (1) Utilizes less water (for WAD 83.5 l/t OFMSW, for HSAD no extra water is added); (2) produces almost 2.5 times more biofertilizer, with roughly 233 kg/t OFMSW compared to 100 kg/t OFMSW of the WAD plant; (3) it has significantly higher energy efficiency with an energy ratio (ER) of 26.4 %, whereas for WAD the ER is 68 %; and, (4) it presents a significant GHG mitigation potential, reaching yearly savings of 3,892,587.56 kg CO2eq. With this, HSAD proves to be a suitable solution for the Brazilian conditions and offers tangible diverse benefits to treat the OFMSW.